THE OMISSION OF GRAMMATICAL COMPONENTS: ERRORS AND ITS EFFECTS ON STUDENT'S ACADEMIC WRITING QUALITY - Zulfariati Zulfariati (LPPM Universitas Ekasakti, 2021)
Grammatical errors have been a major issue for decades. Some researchers have analyzed many types of grammatical errors made by foreign language students of English. This paper is one of the descriptions of grammatical errors derived and developed by the English Department of FKIP UMMY Solok in writing their theses. The students’ theses which had been allowed for joining the final comprehensive exam for getting the strata one degree at English Department of FKIP UMMY Solok were analyzed. Ideally, those theses were written by using correct grammar. However, there were still many errors in those theses. The errors found were respectively in form of omission, addition, misformation, and misordering types. This article focuses on the description of the omission of grammatical components written by the students and how it affects their theses quality. Admittedly, these grammatical errors make the theses quality are low and the ideas of the writing are difficult to be caught by the readers because some of the head nouns, subjects, verbs, direct objects, and other components of some sentences in those theses were omitted. It is suggested that the lectures on Grammar and Writing subjects as well as the students’ advisors on academic writings do intensive corrections towards students’ theses.